1980
DOI: 10.1016/s0022-5347(17)55378-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Inside Echo Patterns in Gray Scale Prostatic Echography

Abstract: Improved gray scale echograms in transrectal ultrasonography clearly can visualize the anatomical structure of and pathological changes in the prostatic gland. This study includes the classification of ultrasonic findings from the prostatic gland into acoustical pattern groups--solid, cystic and mixed--as well as into pathological-anatomical pattern groups--internal gland, external gland, nodule, stone and miscellaneous. The diagnostic accuracy of prostatic diseases using pattern analysis of prostatic inside e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1982
1982
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(19 citation statements)
references
References 9 publications
2
17
0
Order By: Relevance
“…Of note, there is a large difference in the detection rate of prostatic calculi using X-rays and that using ultrasonography. Harada et al [26] reported that 80% of calculi are identified with TRUS, but that X-ray only identifies 28% of the calculi. In addition, Peeling et al [27] found that > 70% of prostate calculi images were identified with TRUS, which were not visualized with X-rays.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, there is a large difference in the detection rate of prostatic calculi using X-rays and that using ultrasonography. Harada et al [26] reported that 80% of calculi are identified with TRUS, but that X-ray only identifies 28% of the calculi. In addition, Peeling et al [27] found that > 70% of prostate calculi images were identified with TRUS, which were not visualized with X-rays.…”
Section: Discussionmentioning
confidence: 99%
“…Tewari et al [9] concluded that TRUS was inexpensive, easy to use, noninvasive and accurate when compared with MRI. Harada et al [13] showed that the adenoma could be differentiated on TRUS from normal prostatic tissue in patients with BPH, and Jones et al [14] distinguished adenoma from normal prostate using transabdominal ultrasonography. In the present study, adenoma was easily distinguished from total prostate tissue, allowing an estimate of their respective weights.…”
Section: Discussionmentioning
confidence: 99%
“…2, 3). The capsular echoes become continuous, while the internal echoes decrease and are symplified (Watanabe et al 1974b(Watanabe et al , 1981Harada et al 1980).…”
Section: Resultsmentioning
confidence: 99%